Judicial fine: problems of substantive basis and law enforcement practice - A. V. Boyarskaya (Правоприменение, 2018)
The subject of the article is the grounds for exemption from criminal liability with the appointment of a judicial fine are being considered.The purpose of the article is to reveal the systemic links between Art. 76.2 and 75-76 of the Criminal Code of the Russian Federation as well as prospects of judicial fine in criminal law.The methodology of research includes methods of complex analysis, synthesis, as well as formal-logical, comparative legal and formal-legal methods.Results, scope of application. The author analyzes the practice of applying Art. 76.2 of the Criminal Code of the Russian Federation on criminal cases concerning crimes with a formal composition, when the defendants did not make any compensation for damage or other reparation for damage caused by the criminal act.The author notes that the institution of release from criminal liability with the appointment of a judicial fine is controversial. On the one hand, it has positive aspects, as it directly and unambiguously aims at compensation for damage or other smoothing of the harm caused by the crime. Сriminal legislation of the Russian Federation should more actively provide for the interests of the victim.However, fine also has a number of shortcomings related to the contradictory nature of his normative definition. The institution in question does not have its own substantive legal basis, it is applied to the same range of cases as the grounds for exemption from criminal liability provided for in Art. 75, 76 and partially Art. 76.1 of the Criminal Code. Consequently, its appearance can make a system of measures that stimulate positive postcriminal behavior only more contradictory.The introduction of this institution can contribute to an increase in manifestations of corruption. Judicial fine is appointed only by the court, but the court to exercise its functions in this case does not have the ability to verify the truthfulness of the information on the participation of the accused in the committed crime. So, there is a risk of applying this institution to persons who should be brought to criminal responsibility.This institution is available primarily for wealthy suspects (accused persons) who are capable to reimburse the damage caused by crime immediately and, in addition, within the time limits established by the court to pay a judicial fine.Conclusions. The author comes to the conclusion that the exemption from criminal liability with the appointment of a judicial fine is a truncated form of active repentance.